Sprache im kommunikativen, interaktiven und kulturellen Kontext - Deppermann, Arnulf; Reineke, Silke (Germanistische Sprachwissenschaft um 2020, 2018)
The volume surveys the current state of research on the communicative use of language, its role in interaction, and relationship to culture. The essays present the theoretical foundation and historical development of each research area, illustrated with empirical findings, and propose future directions for linguistics research.